2020
DOI: 10.3389/fsoc.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Covid-19: Rates of Incidence and Deaths in the United States During the First 10 Weeks of the Pandemic

Abstract: The Covid-19 pandemic in the winter and spring of 2020 represents a major challenge to the world health care system that has not been seen perhaps since the influenza pandemic in 1918. The virus has spread across the world, claiming lives on all continents with the exception of Antarctica. Since its arrival in the United States, attention has been paid to how Covid-19 cases and deaths have been distributed across varying socioeconomic and ethnic groups. The goal of this study was to examine this issue during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
153
2
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(172 citation statements)
references
References 17 publications
11
153
2
6
Order By: Relevance
“…16 It is very concerning that recent studies, however limited in number, identi ed that the same subpopulations had higher mortality and hospitalization rates of COVID-19. 17,18 This is consistent with prior studies that demonstrated lower education and income resulted in poor outcomes in other diseases. 15,[19][20][21] It is likely that the worse health outcomes of these disadvantaged subpopulations are the result of the lack of effective COVID-19 prevention and coping strategies stemming from the inadequate COVID-19 knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…16 It is very concerning that recent studies, however limited in number, identi ed that the same subpopulations had higher mortality and hospitalization rates of COVID-19. 17,18 This is consistent with prior studies that demonstrated lower education and income resulted in poor outcomes in other diseases. 15,[19][20][21] It is likely that the worse health outcomes of these disadvantaged subpopulations are the result of the lack of effective COVID-19 prevention and coping strategies stemming from the inadequate COVID-19 knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…All regression models included cumulative test rates per 100 000 population. Given the variations in testing capacity and protocols for whom to test, both across states and within states over the study period, 20 changes in detected cases following SAHOs may be an artifact of changes in testing; therefore, controlling for level of testing is critical. Models included a quadratic time-trend measured in days.…”
Section: Methodsmentioning
confidence: 99%
“…While recent studies have documented greater COVID-19 incidence and fatality rates in U.S. counties containing higher proportions of non-White and socioeconomically disadvantaged residents, 10 , 11 , 12 research on the socio-spatial distribution of COVID-19 burdens has paid limited attention to PwDs. To address this gap, this article presents the first national scale study of the relationship between confirmed COVID-19 cases and disability characteristics in the U.S.…”
Section: Introductionmentioning
confidence: 99%